FRI0236 Associations between comorbidity and urate deposition in subjects with asymptomatic hyperuricemia: a pilot study. (12th June 2018) - Kerr, G.; Dowell, S.; Wells, A.; Haddad, R.; DeMarco, P.; Joseph, J.; Ude, J.; Hochberg, S.; Huang, J.; Nashel, D.
Abstract : Background: Hyperuricemia is common and along with comorbidities, is increasing in prevalence. Though often asymptomatic and hence, under diagnosed, it may be associated with subclinical urate deposition. Ultrasound (US) imaging can detect urate deposition in individuals with asymptomatic hyperuricemia (ASU). Objectives: To evaluate the association of comorbidities with urate deposition via US in ASU. Methods: ASU was defined as serum urate (sUA) >6 mg/dl; sUA <6 mg/dl served as controls. Demographic (age, gender, BMI), comorbidity (CM – [hypertension (HTN), hyperlipidemia (HLD), diabetes mellitus (DM), cardiovascular (CVD) and renal disease (CKD)], diuretic/aspirin use, dietary data (alcohol, red meat, seafood) were collected. Ultrasonography (US) of joints (knee/MTP), tendons (triceps, quadriceps/patella, Achilles) was performed via standard procedure, OMERACT parameters of urate deposition documented, and images read by an Expert ultrasonographer blinded to sUA category. Correlations between sUA levels and MSK urate deposition with comorbidities, medication and dietary risk factors were analysed by 2-stage multivariable logistic regression model with propensity score weighting. Results: Of 95 predominantly non-Hispanic Blacks (mean age 59.7 years, BMI 32 kg/m 2 ), ASU subjects (n=71, median sUA=8.0) were older men, with more frequent HTN, CVD, CKD, alcohol ingestion versus controls. In multivariate analyses adjusting for demographic characteristics, BMI, CKD, and alcohol use were positively associated with sUA >6 mg/dl; while HTN, CVD, and CKD were positively associated with sUA >8 mg/dl. Adjusting for comorbidities, sUA >8 mg/dl was significantly associated with urate deposition at knee (OR=3.20; p=0.03), quadriceps and Achilles tendons (OR=4.14; p<0.01), OR=9.51; p<0.01, respectively) but not at 1 st MTP (OR=2.14; p=0.06). A sUA >6 mg/dl alone, however, did not predict urate deposition. Conclusions: Presence of HTN, CVD and CKD are associated with higher levels of sUA and increases the risk of urate deposition in ASU patients. Identifying a subset of ASU patients that may benefit from urate lowering therapy requires further stratification and long term follow up for incident gouty arthritis in order to alter current urate lowering treatment guidelines. Disclosure of Interest: G. Kerr Grant/research support from: Ardea, Grunenthal, Horizon, S. Dowell Grant/research support from: Horizon, A. Wells: None declared, R. Haddad: None declared, P. DeMarco: None declared, J. Joseph: None declared, J. Ude: None declared, S. Hochberg: None declared, J. Huang: None declared, D. Nashel: None declared